Otonomi Khusus dalam Penanaman Modal Dan Permasalahan Hukum Yang Terkait - Sanusi Bintang (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: Article 165 verse (2) of Law Number 11 on Governing of Aceh states that the Government of Aceh and the government of district and municipality based on its authority may provide license related to investment, both domestic and foreign, by reference to national standard operational procedures. Article 165 verse (5) adds that further stipulations concerning the license will be regulated in local laws (qanun). For this purpose, the Aceh Qanun Number 5 of 2009 on Investment has been promulgated. However, there are still legal obstacles in developing both domestic and foreign investment in Aceh. The purpose of this review is to understand and elaborate several stipulations in central government legislation and regulation which are potentially hindrance the investment in the Province of Aceh and also to understand and elaborate several  stipulations in provincial government legislation and regulation which are potentially hindrance investment in Aceh. Data for this review were obtained through juridical legal research. Besides, as additional, researcher/reviewer also conducted interview with informants. The finding shows that stipulations in legislation and regulation of central government which are hindrance investment can be found in various sources  including UUPM, UUKPB PBS, UUPT, UUK, UUKeh., UUP, UUPAg, and Permenkeu. Whereas, stipulations in provincial government legislation and regulation which are hindrance investment can also be found in various sources including QAPM, QPK, QPPK and QPPSDKP. Special Autonomy in Investment and Related Legal Issues